2001
DOI: 10.1093/emboj/20.15.3938
|View full text |Cite
|
Sign up to set email alerts
|

Novel modular domain PB1 recognizes PC motif to mediate functional protein-protein interactions

Abstract: Modular domains mediating speci®c protein±protein interactions play central roles in the formation of complex regulatory networks to execute various cellular activities. Here we identify a novel domain PB1 in the budding yeast protein Bem1p, which functions in polarity establishment, and mammalian p67 phox , which activates the microbicidal phagocyte NADPH oxidase. Each of these speci®cally recognizes an evolutionarily conserved PC motif to interact directly with Cdc24p (an essential protein for cell polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
209
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(212 citation statements)
references
References 44 publications
3
209
0
Order By: Relevance
“…The region of p40 phox involved was reported as the PC motif (residues 287-302) (Nakamura et al, 1998;Ito et al, 2001), now referred as the OPR-PC-AID (OPCA) motif (Ponting et al, 2002). Later, Wilson et al (2003) showed that Thr337 and Pro339 in the region C-terminal region also participate in the heterodimerization.…”
Section: Discussionmentioning
confidence: 99%
“…The region of p40 phox involved was reported as the PC motif (residues 287-302) (Nakamura et al, 1998;Ito et al, 2001), now referred as the OPR-PC-AID (OPCA) motif (Ponting et al, 2002). Later, Wilson et al (2003) showed that Thr337 and Pro339 in the region C-terminal region also participate in the heterodimerization.…”
Section: Discussionmentioning
confidence: 99%
“…is expected from the sequence alignment of the PB1 domain (Fig. 1), the binding assays for an aPKC-ZIP/p62 complex formation have been performed using a much longer construct of PKC -(1-107) (7,9,32,38,39). Interestingly, p40 phox PB1 required more C-terminally extended residues out of the alignment in order to interact with p67 phox PB1, whereas Cdc24p PB1 did not require such a residual region to bind with Bem1p PB1 (35).…”
Section: Preparation Of Pkc -(16 -99)-complementarymentioning
confidence: 99%
“…DNA fragments encoding PKC and ZIP/p62 were prepared as described previously (9). Human PKC -(16 -99) was expressed in Escherichia coli strain BL21 (DE3) cells as a glutathione S-transferase (GST) fusion protein.…”
Section: Preparation Of Pkc -(16 -99)-complementarymentioning
confidence: 99%
See 2 more Smart Citations